Construct Validity Evidence in the Motor Coordination Test with Ball - MCTB. Issue 4 (August 2022) - Ribas, Schelyne; Aburachid, Layla M. C.; Marôco, João; Mazzardo, Tatiane; de Oliveira Castro, Henrique; Greco, Pablo Juan
Our purpose with this study was to analyze construct validity evidence for the Motor Coordination Test with Ball (MCTB). Our participant sample included 1620 students (741 girls; 879 boys) aged between 10-12 years. Evidence for construct-validity of the four tasks using exploratory factor analysis (EFA) and adequacy indices confirmed a good fit of a final two-dimensional model (BTS = .000; KMO = .83; loading .53 to .91; communalities ranging from .31 to .86; explained variance of 63.5%; goodness-of-fit index (GFI) = .99; adjusted GFI (AGFI) = .97; RMSR = .03), and confirmatory factor analysis (CFA) (X 2 /df = 4.9; GFI = .97; comparative fit index (CFI) = .92; TLI = .90; Root-Mean-Square Error of Aproximation (RMSEA) = .03). We concluded that, in a Brazilian sample, the MCTB has good construct validity for motor coordination tests with balls; this helps qualify this test for use in schools and in the sports context.